Implementasi Shalat Dzuhur Berjamaah dalam Meningkatkan Karakter Disiplin di Madrasah Ibtidaiyah: The Implementation of Congregational Dhuhr Prayer in Enhancing Discipline Character at Madrasah Ibtidaiyah - Maulida, Dela; Khoerotunnisa, Khoerotunnisa; Permana, Galih; Nurjariah, Fatimah (Perkumpulan Peneliti dan Pegiat Literasi, 2025)
This study evaluates the implementation of congregational Dhuhr prayers in shaping the disciplined character of students at MI Daarussalaam. It emphasizes the role of habitual worship as a foundation for character education in a school setting. Using a qualitative approach with a phenomenological design, data were collected through interviews and observations. The findings reveal that while the congregational prayer program has been implemented, not all students consistently participate. Teachers play a vital role in motivating students and serving as role models to enhance their discipline. The study highlights that the practice of congregational prayers can effectively shape disciplined character when supported by active family involvement and increased self-awareness among students. Limitations of the study include minimal family engagement and the short duration of the research. Future research is recommended to conduct long-term evaluations and establish collaborative programs between schools and families to maximize the program's impact. This study contributes to the discourse on character education, particularly within the framework of religious education in primary schools.